Morin hydrate loaded solid lipid nanoparticles: Characterization, stability, anticancer activity, and bioavailability. (November 2020) - Karamchedu, Swathi; Tunki, Lakshmi; Kulhari, Hitesh; Pooja, Deep
Highlights: Morin hydrate loaded solid lipid nanoparticles (MSN) were prepared and characterized. MSN were < 100 nm in size and encapsulated about 87 % of drug. MSN showed in-vitro anticancer activity against human cervical cancer cells. The bioavailability of morin hydrate was improved significantly after administration as MSN. Abstract: Nanotechnology has come up as a protean field integrating concepts of alternate drug delivery systems using nanocarriers. The idea of encapsulating a drug molecule into a colloidal carrier like solid lipid nanoparticle has been a promising approach for development of nanomedicines. In this research work, a hydrophobic, natural, and an anticancer bioflavonoid, morin hydrate (MH) was encapsulated into solid lipid nanoparticles to overcome the issues of its poor aqueous solubility and low oral bioavailability. The prepared morin hydrate loaded solid lipid nanoparticles (MSN) were characterized by DLS, FTIR, and DSC analysis. The MSN showed nanoscale size, good steric stability, and release in simulated intestinal fluid. The in-vitro anticancer studies against human cervical cancer cells revealed the higher cytotoxicity of encapsulated MH than free or pure MH. MSN also demonstrated a significant improvement in pharmacokinetics of encapsulated MH.